Difficulties in the Incorporation of Augmented Reality in University Education: Visions from the Experts - Julio Barroso Osuna; Juan Jesús Gutiérrez-Castillo; Mª del Carmen Llorente-Cejudo; Rubicelia Valencia Ortiz (Springer, 2019)
"Augmented reality" (AR) is presented as technology that harmonizes, in real time and with user collaboration, digital information with physical information through different technological supports. Such are AR possibilities, that when it is incorporated into teaching, students show high satisfaction rates and positive attitudes for its use, but at the same time, a series of limitations and obstacles can be noticed. As an attempt to investigate the technical, curricular and organizational difficulties of AR incorporation in training contexts, an instrument "AR obstacle questionnaire" (CORA) was designed, which in turn was administered to a total of 264 subject experts for validation through the Delphi method, subsequently applying the "K coefficient" (K = ½ Kc (knowledge coefficient) + Ka (argumentation coefficient)), selecting those experts who obtained a ≥ 0,8 score in the coefficient. Among the results obtained in the study we manage to point out the main obstacles involving AR implementation into university education: the lack of teacher training and improvement, the few educational experiences found, lack of conceptual foundation, limited educational research and lack of institutional support.